Ultrathin CoPt alloy films with fcc (111) orientation and perpendicular magnetic anisotropy fabricated by electrodeposition - Daiki Araki; Yoshiaki Sonobe; Yukiko K. Takahashi; Takayuki Homma (Electrochemistry Communications)
In this study, ultrathin CoPt alloy films oriented along face-centered cubic (fcc) (111) with perpendicular magnetic anisotropy (PMA) are fabricated by electrodeposition at room temperature and normal pressure without annealing. By increasing the concentration of Pt ions in the electrolytes, initial nucleation of CoPt becomes fine, forming epitaxial CoPt alloy films oriented along fcc (111) to the film planes with very smooth surfaces (Arithmetic average roughness Ra ∼ 0.43 nm). The deposited CoPt films show the lower saturation magnetization (MS ∼ 620 emu･cm−3) compared to conventional CoPt films with hexagonal close-packed (hcp) structures. The CoPt film with a thickness of 5 nm exhibits large PMA (anisotropy constant Ku ∼ 4.3 Merg･cm−3), coercivity (HC ∼ 2.4 kOe), and nucleation field (Hn ∼ 2.0 kOe). The fabricated CoPt films contribute to the development of magnetic tunnel junctions with enhanced tunnel magnetoresistance effects and a next-generation magnetic memory with ultrahigh recording density.